Challenges and Possibilities of Archaeological Sites Virtual Tours: The Ulaca Oppidum (Central Spain) as a Case Study - Miguel Ángel Maté-González; Jesús Rodríguez-Hernández; Cristina Sáez Blázquez; Libertad Troitiño Torralba; Luis Javier Sánchez-Aparicio; Jesús Fernández Hernández; Tomás Ramón Herrero Tejedor; José Francisco Fabián García; Marco Piras; Carlos Díaz-Sánchez; Diego González-Aguilera; Gonzalo Ruiz Zapatero; et al. (Remote Sensing, 2022)
This research presents a virtual tour performed on the oppidum of Ulaca, one of the most relevant archaeological sites of the Iberian Peninsula during the Late Iron Age (ca. 400–50 BC). Beyond the clear benefits of the tool to the interpretation, dissemination, and knowledge of the mentioned archaeological site and its surroundings, the novelty of this research is the implementation of the platform in alternative scenarios and purposes. In this way, the present work verifies how the access to multi-source and spatially geolocated information in the same tool (working as a geospatial database) allows the promotion of cross-sectional investigations in which different specialists intervene. This peculiarity is also considered useful to promote tourism with an interest beyond the purely historical/archaeological side. Likewise, the possibility of storing and managing a large amount of information in different formats facilitates the investigation in the contexts of excavations and archaeological or environmental works. In this sense, the use of this kind of tool for the study of cultural landscapes is especially novel. In order to better contextualize the potential of the virtual tour presented here, an analysis about the challenges and possibilities of implementing this tool in environments such as the Ulaca oppidum is performed. The selected site stands out for: (i) being in a unique geological, environmental and ecological context, allowing us to appreciate how human beings have modified the landscape over time; (ii) presenting numerous visible archaeological remains with certain conservation problems; and (iii) not having easy access for visitors.